Characterization of zinc oxide-based varistor ceramics prepared using solid state route and co-precipitation processing - Mohd Ghazali, Mohd Sabri (2013)
There were few reports of fabrication of varistor ceramics that used as a protective device for electrical equipments from transient voltage surges, using other method than conventional solid-state. Hence, it is useful to characterize in terms of morphology, electrical non-linearity characteristics, and optical properties of it prepared by using co-precipitation processing, as this produces fine and homogenous powder, as well as conventional solid-state route. The objectives of the study are; to prepare four systems of ZnO based varistor ceramics through conventional solid-state route and co-precipitation technique to determine which factors affect most on electrical non-linearity behavior; secondly to carry out optical study of four systems of ZnO based varistor ceramics obtain from conventional solid-state route and co-precipitation technique to elucidate the structure arrangement; and thirdly to investigate the degradation behavior of one system of ZnO based varistor ceramics (ZnO-Bi2O3-TiO2) to ascertain which preparation technique produce most stable electrical non-linearity coefficient. For the methodology, the prepared samples from co-precipitation and solid-state route were examined with EDX microanalysis for chemical and physical examinations, SEM and FESEM for morphological examinations, XRD and optical microscopy for crystallographic examinations, UV-visible spectroscopy for optical band gap measurements and structure arrangement observation, and the I-V measurements for non-linearity characteristic. The selected samples were subjected simultaneously to stresses of specific temperature, and DC voltage over certain duration to study the degree of degradation. In this study, with the use of different additives, secondary phases are developed and coexisted in the varistor ceramics that are Bi4Ti3O12, Zn2TiO4, and Zn7Sb2O12 as a grain inhibitor and segregated at the grain boundaries and the triple point junctions. The development of these secondary phases influences the varistor ceramics performances in electrical and optical properties as well as in degradation percentage. Average density of the ceramics at all combination has the same trend where it increases with the increase of doping concentration, sintering time and temperature, as Bi2O3, MnO2 and TiO2 are strong grain enhancers. The additive of Sb2O3 is a strong grain inhibitor which produces secondary phases, Zn2Bi3Sb3O14 at low and Zn7Sb2O12 at high doping concentrations. The important findings here is that α value of solid-state route samples is optimum at 4.56, 10.36 and 5.36 at 45 min sintering time for System 2, System 3 and System 4 that used consecutive addition of Sb2O3, MnO2 and Co3O4, respectively. While α is optimum at 9.59, 10.48 and 15.42 at 45 min sintering for System 2, System 3 and System 4, respectively, which fabricated by co-precipitation processing. In addition, the electrical properties of ZnO based varistor ceramic doped with different additives are investigated in conjunction with the optical properties such as optical band-gap (Eg) and structural arrangement. Here, the Eg of the ZnO varistor ceramics and non-linearity behavior varies with the different additives and processing conditions. The Eg decreases due to the increase in the structural disordering which incorporation with the growth of interface state in the forbidden band-gap region and vice versa. Degradation has caused a decrease in varistor voltage and an increase in leakage current. After exposure to DC and heat stresses simultaneously for 12 h, the varistor ceramics experiences a slight drop in grain boundary resistances. Thus, the varistor ceramic samples exhibit high level of leakage current compared to initial state which indicates they have been degraded or deteriorate. In addition, higher leakage current signifies that samples experience greater watt loss during stress. In practice, high watt loss is unfavorable because it can increased energy consumption and increased the potential for thermal runaway. The degradation percentage was calculated in term of changes in varistor voltage before and after stresses and it shows that samples fabricated by solid-state route especially at three particular sintering temperatures of 45.min sintering time which are 1140, 1170 and 1260.oC, possess low degradation percentage as the value is 10% or below. From these criteria and as compared to I-V characteristics behavior, it is believed that the sintered samples at 1140.oC of 45.min sintering is relatively stable which does not show significant change in α, barrier height, and relative ratio of the nonlinear voltage (at 1.mA) for solid-state route samples. The percentages of the relative ratio of nonlinear voltage of all samples by co-precipitation processing exhibit low than 10%. From this result, samples fabricated by co-precipitation processing is relatively more stable that capable to withstand further stresses, low watt loss, low potential for thermal runaway and thus low energy consumption.